Effects of the Screw-Access Hole Diameter on the Biomechanical Behaviors of 4 Types of Cement-Retained Implant Prosthodontic Systems and Their Surrounding Cortical Bones: A 3D Finite Element Analysis. Issue 5 (October 2018) - Du, Liangzhi; Li, Zhe; Chang, Xiaofeng; Rahhal, Omar; Qin, Bowen; Wen, Xi; Zhou, Dangxia
Abstract : Purpose: To investigate the effect(s) of screw-access hole (SAH) in different diameters on the cement-retained implant prosthodontic systems and surrounding cortical bones. Materials and methods: Twenty finite element models were divided into 4 groups: 2 types of full-contour (FC) crowns (Y-TZP, gold alloy) and 2 types of porcelain-fused-to-metal crowns (based on Co-Cr, Au-Pd alloy). For each group, 5 crowns were simulated by varying the diameter of SAH (0, 1, 2, 3, and 4 mm). A vertical load of 200 N and an oblique load of 100 N (45°s) were applied. All models were analyzed with finite element analysis software. Results: The stress on the occlusal surface of crowns was almost unchanged when the SAH was within 0 to 3 mm, whereas it showed an obvious increase when it reached 4 mm. The stress concentration was also suddenly changed from the loading area to the hole margin under vertical loading. As for the screw, a lower stress level was observed in vertical loading when an FC crown with an SAH within 0 to 1 mm was applied. The stress concentration was constantly located at the beginning of the first thread. Stresses of other components remained almost unchanged. Conclusions: From the aspect of biomechanics, an FC crown with a 1-mm access hole is recommended when a combined cement- and screw-retained crown was used in the posterior region.